2020
DOI: 10.1155/2020/9247237
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Frailty and Erectile Dysfunction among Chinese Elderly Men

Abstract: Objective. This study is aimed at assessing association between frailty and erectile dysfunction among Chinese elderly men. Methods. This community-based study was conducted with a sample of 341 Chinese elderly men (aged 60 to 83 years old) in Fuyang City (Anhui Province, China). Each of the participants completed a standard questionnaire, including demographics (age, height, weight, yearly income, educational status, comorbidity, lifestyle factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…Furthermore, frailty was associated with impaired general sexual functioning, suffering related to sexual function and erectile dysfunction (30). Another Chinese community-based study conducted with 341 men older adults aged 60 to 83 years old revealed a strong association between erectile dysfunction and frailty among the participants, evidencing the need to consider erectile dysfunction in multidimensional assessments of frailty (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, frailty was associated with impaired general sexual functioning, suffering related to sexual function and erectile dysfunction (30). Another Chinese community-based study conducted with 341 men older adults aged 60 to 83 years old revealed a strong association between erectile dysfunction and frailty among the participants, evidencing the need to consider erectile dysfunction in multidimensional assessments of frailty (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between age and ED. But most of these studies have focused on older men or men whose average age was over 40 years [ 22 25 ]. The absence of such an association in our study appears to be due to the low average age (approximately 30 years) of men with GWs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el COVID-19 podría exacerbar condiciones cardiovasculares preexistentes, pudiendo incrementar el riesgo de padecer DE 33 , considerando además, que el sexo masculino ha sido asociado a casos más severos de infección debido al SARS-CoV2 37 . Aun cuando la DE incrementa con la edad, la evidencia disponible menciona que la DE es significativamente mayor en sujetos > 60 años que personas menores de 60 años años 43,44 . De acuerdo con nuestros análisis, se encontró que, pese a que existían diferencias significativas de edad entre los grupos No SDRA 38,4 años (± 14,9) y el SDRA 48,9 años (± 11,7), estas edades no generan diferencias significativas entre los puntajes del IIEF5 en los modelos univariados y multivariados.…”
Section: Discussionunclassified